2011
DOI: 10.1016/j.taap.2010.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and hepatic stellate cell activation are key events in arsenic induced liver fibrosis in mice

Abstract: Arsenic is an environmental toxicant and carcinogen. Exposure to arsenic is associated with development of liver fibrosis and portal hypertension through ill defined mechanisms. We evaluated hepatic fibrogenesis after long term arsenic exposure in a murine model. BALB/c mice were exposed to arsenic by daily gavages of 6 μg/ gm body weight for 1 year and were evaluated for markers of hepatic oxidative stress and fibrosis, as well as pro-inflammatory, pro-apoptotic and pro-fibrogenic factors at 9 and 12 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 48 publications
3
77
0
2
Order By: Relevance
“…As a result the accumulated hydroperoxides in this organ could cause cytotoxicity associated with membrane phospholipids peroxidation, the basis of liver damage. Such results agree with the previous findings (Ghatak et al, 2011;Messarah et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As a result the accumulated hydroperoxides in this organ could cause cytotoxicity associated with membrane phospholipids peroxidation, the basis of liver damage. Such results agree with the previous findings (Ghatak et al, 2011;Messarah et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Epidemiology studies have indicated that chronic arsenic exposure causes abnormal liver function, hepatomegaly, liver fibrosis and cirrhosis (Santra et al, 2000). Subsequent studies of Santra et al (2000) and Ghatak et al (2011) on chronic arsenic toxicity have revealed that oxidative stress and hepatic stellate cell activation are key events in arsenic-induced liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines can enhance the oxidative stress and inflammation, which in return mediate cell differentiation and permeates through whole fibrogenesis process. The modulating mechanisms of genes coding cytokines in HSCs are underlined (Ghatak et al 2011;Ramachandran and Iredale 2012).…”
Section: Epigenetic Modifications In Hsc Promote Oxidative Stress Andmentioning
confidence: 99%
“…2) In recent years, considerably clinical and experimental evidences show that oxidative stress caused by an imbalance between the oxidant and antioxidant systems of the body in favor of the oxidants should be a major apoptotic stimulus in the different types of acute and chronic liver injury and hepatic fibrosis. 3) Carbon tetrachloride (CCl 4 ) is a xenobiotic used extensively to induce oxidative stress. The rats treated with CCl 4 are frequently used to produce an experimental model to study hepatic fibrosis.…”
Section: Hepatoprotective Effects Of Phloridzin On Hepatic Fibrosis Imentioning
confidence: 99%